Marine heatwave decimates fire coral populations in the Caribbean - Emilia C. Dell’Antonio; Lauren Mahoney; Peter J. Edmunds (Proceedings of the National Academy of Sciences, 2025)
Marine heatwaves (MHW) are common destructive events affecting coral reefs. After decades of degradation, the shallow reefs of the United States Virgin Islands have been depleted of scleractinian corals, leaving abundant colonies of the hydrozoan fire coral Millepora dominating the coral community. This dominance ended in 2024 after 84% of Millepora colonies over 43 km of shore were killed by a MHW that brought the hottest October in the 36 y since monitoring began. In August 2024, dead Millepora were rare on these reefs, but by March 2025, severe bleaching created a fire coral graveyard. Decimation of the fire coral biotope shows that these short-term coral winners are unlikely to be future reef builders.